Impact of librarians’ perception towards disaster management in university libraries in South-South, Nigeria - Osawele, Rachael Ekeikhomen; Akpukpu, Omono-vera (Communicate: Journal of Library and Information Science, 2025)
This study investigated the impact of librarians’ perception towards disaster management in university libraries in south-south, Nigeria. The objective of the study was to determine the extent of disaster management, and find out the librarians’ perception regarding disaster management in university libraries in south-south, Nigeria. Two research questions and one research hypothesis were raised, answered and tested. Descriptive survey research design of the correlational approach was adopted for the study. Population of the study was 402 respondents. The study adopted total enumeration sampling technique. The structured questionnaire titled, “Questionnaire on the Impact of Librarians’ Perception towards Disaster Management in University Libraries in South-South, Nigeria, (Q ILPDMULSSN)” was used for data collection. A total of 402 copies of the questionnaire were distributed to the respondents within two weeks and the completed copies of the questionnaire were collected after one week to ensure high retrieval rate of the distributed instrument. The data collected were analysed using descriptive statistics in form of percentage and frequency count, statistical mean (x) and standard deviation SD. The finding revealed that disaster management in university libraries in south- south, Nigeria which includes disaster recovery assists in restoring damaged equipment, physical buildings as well as lives to normalcy (x̄ =3.34), SD = 0.08, is positive. Finding also revealed that librarians' perception regarding disaster management which include disaster management is too broad for university libraries to undertake alone (x = 3.14), SD = 0.07, in university libraries in south-south Nigeria, is positive. The study recommended that the practice of disaster management should be taken seriously by the librarians in order to protect the library buildings and its resources from disasters.